Relationship of Officers’ Performance and Outpatient’s Medical Record Time Provision - Atma Deharja; Irfiah Irfiah; Rossalina Adi Wijayanti; Efri Tri Ardianto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The time for providing outpatient medical records according to the Indonesian Ministry of Health is ≤ 10 minutes. Based on the pre-survey at Hospital “X” using 100 files of outpatient medical records showed that 80% the provision has been a delay. The aim of this study is to analyze the relationship of individuals, organizations, and psychology to the time of providing outpatient medical records. This is an analytic study with a cross-sectional method and the data analysis was carried out bivariate by chi-square test. Individual variables (ability) related to providing a time of outpatient medical records (Sig 0.08), sub-variable skill related to providing time outpatient medical records (Sig 0.061), organizational variables with job design sub-variables not related with providing time outpatient medical records (Sig 0.399). Sub leadership variables related with providing time outpatient medical records (Sig 0.08), psychological variables with attitude variables related with providing time outpatient medical records (Sig 0.015), sub motivation variables not related with providing time outpatient medical records (Sig 0.182). Related variables are individuals (abilities and skills), organizations with sub-leadership variables, psychological with sub attitude variables, meanwhile organizational variables with sub-job design variables, psychological variables with sub motivation variables are not related.